PENGARUH KOMPETENSI DAN KINERJA KARYAWAN TERHADAP PENGEMBANGAN KARIR DI PERUSAHAAN (Studi Kasus di PT WB, Tbk Wilayah Penjualan III Jakarta) - Firman Fauzi; Muhammad Hanafiah Siregar (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2019)
This research was conducted at PT WB with the aim of analyzing the effect of competence and employee performance on career development in a company engaged in the construction industry. This study uses descriptive quantitative research with a sample of 100 respondents as samples as well as populations or called saturated samples. Data analysis using multiple linear regression methods to test the research hypothesis. The results of the study concluded that employee competence has a positive and significant influence on employee career development and employee performance also has a positive and significant influence on employee career development.